Philosophy and counterculture. On Ludwig Wittgenstein’s heterodox metaphilosophical conception - Tejada Sandoval, José Antonio (2025)
The ideas that Wittgenstein formulates about philosophy in his two main works and in some important posthumously published texts, acquires a resoundingheterodox character. This consists of denying philosophy the condition of knowledge, reserving for it, in a first moment, a task that is aimed at the analysis of language, which has the logic as tool, for then, at his second stage of thought, proposing a kind substantially different of analysis, focused on the grammar of expressions. This unique metaphilosophic conception is closely relationated to Wittgenstein’s frontal questioning of the scientific mentality that pervades contemporary society. It is at this point that a space of convergence is to be opened between his perspective and the criticism that the counterculture of the sixties, through thinkers such as Theodore Roszak, will direct to the technocratic society.